A comparison of L-dopa and clonidine growth hormone stimulation tests in children with short stature - Bolu , Semih; Asik , Abdulvahit (Annals of Medical Research, 2022)
Aim: The purpose of this study was to compare the results of L-dopa and clonidine GH stimulation tests in children with short stature and to identify which of these should be primarily selected. Materials and Methods: The records of 68 patients aged between 2.5 and 16.6 years presenting to the pediatric endocrinology clinic with short stature and undergoing GH stimulation tests between September 2016 and February 2021 were evaluated retrospectively. Cases with GH levels <10 ng/ml following the first GH stimulation test then underwent the other GH stimulation test. Thirty-four (50%) of the cases in the study began with the clonidine test and the other 34 (50%) with the L-dopa test. Results: Thirty-five patients (51.5%) were girls and 33 (48.5%) were boys. The clonidine test results was also low in 35 of the 44 patients with peak GH levels <10 ng/ml at the L-dopa test. L-dopa test results were similarly low in 35 of the 37 patients with clonidine test results <10 ng/ml. Chi-square analysis revealed a statistically significant difference between the groups in terms of L-dopa and clonidine measurements (p< 0.001). A cut-off point of 8.9 ng/ml was determined for 50% sensitivity and 100% specificity for the L-dopa test, and a cut-off point of 9.76 for 88% sensitivity and 94% specificity for the clonidine test. Conclusion: GH stimulation tests performed to investigate GHD are laborious and time-consuming. The first stimulation test to be applied to differentiate GHD from ISS must therefore be well selected. The clonidine stimulation test, with higher sensitivity than but similar specificity to the L-dopa test, can be employed as the first test.